INTERAKSI SOSIAL MERUPAKAN FAKTOR YANG PALING BERPENGARUH TERHADAP KEJADIAN DEPRESI PADA LANSIA - Rinna Yulianty; Sri Werdati; Fajriyati Nur Azizah (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: The number of elderly population in Indonesia is predicted to be increasing from 9.77% in 2010 to 11.34% in 2020. Special Region of Yogyakarta has the highest life expectancy in Indonesia (74 compared to 72 years old in Indonesia). Bantul has the highest number of elderly in Yogyakarta, with the total of 113,094 elderly people. Elderly people often suffer from mental health problems, one of the most frequent disorder is depression. Depression in elderly is often undetected because physical problems are more as focus and depression symptoms vary among elderly. Objective: To investigate the characteristics of respondents and to describe factors related to the incidence of depression in the elderly. Methods: This study was non-experimental with descriptive analytic research design using cross sectional approach. Total respondent was 49 elderly, 22 male and 27 female. Samples were collected with a simple random sampling. Data were analysed with proportion test, correlation test, and logistic regression. Results: Age and sex were weakly correlated with the incidence of depression in elderly (0.217 and -0.243, respectively). Social interaction and caregiver support had very strong correlations with the incidence of depression (0,952 and 0,788, respectively). The multivariate statistics test showed that social interaction was the strongest factor which influenced the incidence of depression in the elderly (0,898). Conclusion: Sex and age had weak relationships with the incidence of depression, while social interaction and caregiver support had very strong relationships. Social interaction was the strongest factor related to the incidence of depression in the elderly. Keywords: Depression, caregiver support, elderly, social interaction